2022
DOI: 10.3389/fnut.2022.898849
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 Vaccine Booster Effects Are Seen in Human Milk Antibody Response

Abstract: Infants remain at high risk for severe coronavirus disease 2019 (COVID-19). Human milk contains high levels of protective SARS CoV-2 specific antibodies post-infection and primary vaccine series, but levels decline over time. We hypothesized that the COVID-19 booster vaccine augment antibody production and the protection afforded to human milk-fed infants. We prospectively enrolled pregnant or lactating mothers planning to receive COVID-19 vaccination. We measured human milk IgG, IgA, and IgM antibodies target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…In contrast to that observed for IgA, a significant decreased was observed in IgG levels both in serum and breastmilk pared samples. These results are in agreement with previous studies using mRNA-based vaccines that showed increased IgG levels after the first and second doses, with a significant reduction thereafter ( 35 , 37 , 38 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast to that observed for IgA, a significant decreased was observed in IgG levels both in serum and breastmilk pared samples. These results are in agreement with previous studies using mRNA-based vaccines that showed increased IgG levels after the first and second doses, with a significant reduction thereafter ( 35 , 37 , 38 ).…”
Section: Discussionsupporting
confidence: 93%
“…This rapid increase of IgG after the second dose is consistent with a specific B lymphocyte memory that will prime a faster response with higher antibodies levels ( 33 ). In contrast, we observed that the IgA levels remained constant between the two doses, as it was reported in previous studies with adenoviral-based vaccines (Ad26.COV2.S and ChAdOx1‐S) ( 27 , 28 , 35 ). Heterogeneous dynamics in IgG and IgA antibody levels can be associated to their diverse functions.…”
Section: Discussionsupporting
confidence: 82%
“…24 Our results confirm earlier conclusions that the initial two dose vaccination series during gestation resulted in appreciable RBD-specific IgG response in maternal circulation, UCB, and breastmilk. 20, 27 Importantly, longitudinal analysis of post-partum samples indicates that the booster dose is essential for producing higher and more durable antibody levels in both maternal circulation and breastmilk, 28, 29, 42 and should be strongly encouraged for all pregnant people to increase neonatal passive immune protection against SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…20, 27 Moreover, booster vaccinations led to increased levels of maternal IgG1 and IgA antibodies in umbilical cord blood 28 and breastmilk. 29…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation